Outcomes with newly proposed classification of acute respiratory deterioration in idiopathic pulmonary fibrosis. (October 2018) - Teramachi, Ryo; Kondoh, Yasuhiro; Kataoka, Kensuke; Taniguchi, Hiroyuki; Matsuda, Toshiaki; Kimura, Tomoki; Yokoyama, Toshiki; Yamano, Yasuhiko; Furukawa, Taiki; Sakamoto, Koji; Hashimoto, Naozumi; Hasegawa, Yoshinori
Abstract: Background: Respiratory-related hospitalization, in particular acute exacerbation of idiopathic pulmonary fibrosis (AE-IPF), is common and associated with increasing mortality in patients with IPF. We aimed to evaluate the implications of a newly proposed framework of acute respiratory deterioration (ARD) and AE-IPF in hospitalized patients. Methods: Using the data of an IPF cohort consisting of 225 consecutive patients, we retrospectively studied first hospitalizations from January 2008 to December 2017. We analysed the demographics and 90-day mortality of patients with AE-IPF and those with parenchymal cause of ARD other than AE. Results: Among 122 patients with first hospitalization for ARD, 35 patients were diagnosed with AE-IPF, including 11 patients with triggered AE. Parenchymal cause of ARD other than AE was diagnosed in 71 patients, and extra-parenchymal cause in 16 patients. Almost all hospitalized patients (93%) underwent chest CT, and 83% of patients with AE-IPF underwent bronchoalveolar lavage. There was a significant difference in the anti-inflammatory therapy between the AE-IPF group and parenchymal cause of ARD other than AE group (p < 0.001). AE-IPF was independently associated with poor survival in multivariate Cox proportional regression analysis. Conclusions: AE-IPF accounted for about 30% of first hospitalizations for ARD, and differentiation between AE-IPF and the other categories in ARD is important from a therapeutic and a prognostic point of view. Highlights: AE-IPF accounted for about 30% of first hospitalizations for ARD. AE-IPF was independently associated with poor survival. Therefore, differentiation between AE-IPF and other parenchymal causes is important.